Nitrogen factors for rainbow trout (Oncorhynchus mykiss) and brook trout (Salvelinus fontinalis) fillets - Honzlova, Alena; Curdova, Helena; Schebestova, Lenka; Bartak, Pavel; Stara, Alzbeta; Priborsky, Josef; Sandova, Marie; Koubova, Anna; Svobodova, Zdenka; Velisek, Josef (Veterinarni medicina, 2022)
Measures for consumer protection against food adulteration and misleading labelling are integrated into EU legislation, including methods for detecting misleading practices. Verification of the meat content is available for marine products, but not for salmonid fish due to the lack of standard nitrogen factors. This study aimed to establish nitrogen factors for rainbow trout (Oncorhynchus mykiss) and brook trout (Salvelinus fontinalis). The study analysed 340 fish from Czech fisheries obtained in the summer of 2018-2020. According to the established ISO methods, fillet samples with and without skin were analysed for their nitrogen content (protein), dry matter, ash, and fat. The recommended nitrogen factor for rainbow trout fillets with and without the skin is 3.07 ± 0.12 and 3.06 ± 0.14, respectively, and the nitrogen factor for fat-free rainbow trout fillets with and without the skin is 3.33 ± 0.15 and 3.29 ± 0.15, respectively. The recommended nitrogen factor for brook trout fillets with and without the skin is 3.16 ± 0.10 and 3.12 ± 0.09, respectively, and the nitrogen factor for fat-free brook trout fillets with and without the skin is 3.42 ± 0.13 and 3.36 ± 0.12, respectively. The established nitrogen factors will enable the analysis of the meat content to ensure that consumers purchase correctly described and labelled fish products.
Keywords: fish products; fish-food fraud; adulteration; salmonid; nitrogen factor